Implementation of the Papua Province Special Autonomy Policy in a Public Policy Perspective - Muhammad Mussad (ijd-demos, 2022)
Abstract The prolonged battle in Papua has resulted in various multifaceted setbacks, most of which are ignored by the international community. The people of Papua faced a loss that hit them very hard. The purpose of this piece is to examine how certain autonomy policies have been put into practice in Papua Province. The methodology that is used is qualitative. The study that was conducted, which was found in a variety of books and journals, was utilized to compile the data that was employed. The image that can be discovered in this article illustrates the fact that the implementation of the special autonomy has not been carried out in an effective and efficient manner. There is still a long way to go before indicators of the performance of public services and the settlement of conflicts can be considered perfect. In order for the government to arrive at the conclusion that the policy of granting special autonomy cannot necessarily be implemented in a pragmatic manner, it must take humanist approaches that promote a sense of humanity. Keywords: Implementation, Policy, Special Autonomy, Public Policy. AbstrakPertempuran berkepanjangan di Papua telah menghasilkan berbagai kemunduran multifaset, yang sebagian besar diabaikan oleh dunia internasional. Orang Papua menghadapi kerugian yang sangat memukul mereka. Tujuan dari bagian ini adalah untuk mengkaji bagaimana kebijakan otonomi tertentu telah dipraktekkan di Provinsi Papua. Metodologi yang digunakan adalah kualitatif. Kajian yang dilakukan, yang ditemukan dalam berbagai buku dan jurnal, digunakan untuk mengumpulkan data yang digunakan. Gambaran yang dapat ditemukan dalam artikel ini menggambarkan fakta bahwa pelaksanaan otonomi khusus belum dilaksanakan secara efektif dan efisien. Jalan masih panjang sebelum indikator kinerja pelayanan publik dan penyelesaian konflik dapat dikatakan sempurna. Agar pemerintah sampai pada kesimpulan bahwa kebijakan pemberian otonomi khusus tidak serta merta dapat dilaksanakan secara pragmatis, harus dilakukan pendekatan humanis yang mengedepankan rasa kemanusiaan. Kata kunci: Implementasi, Kebijakan, Otonomi Khusus, Kebijakan Publik.